2020
DOI: 10.1371/journal.pone.0231940
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of postnatal depression and its associated factors in Africa: A systematic review and meta-analysis

Abstract: Introduction Postnatal depression (PND) is a major cause of negative health-related behaviors and outcomes during infancy, childhood and adolescent period. In Africa, the burden of postnatal depression is high. However, it is under-investigated hence under-treated. To fill this information gap and to advise further interventions, we aimed at analyzing its epidemiology in Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
5
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 91 publications
6
72
5
3
Order By: Relevance
“…The ndings of this study suggest that rates of antenatal depressive symptoms are high in Rwanda with more than one in four pregnant women in this study having scores in the depressive range. This study reveals a high prevalence of antenatal depressive symptoms compared to other African countries such as Malawi (19%) [1], Ethiopia (16%) [24] but similar to the ndings of a previous assessment of the pooled prevalence of antenatal depression in Africa overall (26.3%) in a recent 2020 systematic review [5]. A previous community-based study in Rwanda using same EPDS cut-off [18], however that showed lower prevalence.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The ndings of this study suggest that rates of antenatal depressive symptoms are high in Rwanda with more than one in four pregnant women in this study having scores in the depressive range. This study reveals a high prevalence of antenatal depressive symptoms compared to other African countries such as Malawi (19%) [1], Ethiopia (16%) [24] but similar to the ndings of a previous assessment of the pooled prevalence of antenatal depression in Africa overall (26.3%) in a recent 2020 systematic review [5]. A previous community-based study in Rwanda using same EPDS cut-off [18], however that showed lower prevalence.…”
Section: Discussionsupporting
confidence: 86%
“…Hence, there is growing evidence that antenatal depression not only affects pregnancy and neonatal outcomes, but also leads to postnatal depression and has in uence on offspring's cognitive development, emotions and behaviors in childhood [4]. However, despite its adverse effects on maternal and child health, less known about the magnitude and risk factors of maternal depression during pregnancy in developing countries [5], and antenatal depression is often overlooked in routine screening [6].…”
Section: Introductionmentioning
confidence: 99%
“…All of the studies conducted in South Africa, Malawi and Ethiopia identified a high prevalence of postpartum depression (34, 26 and 33%, respectively) but failed to identify the effect of postpartum depression on exclusive breast feeding practices [ 24 , 25 , 60 ]. Whereas, in this review the prevalence of postpartum depression in Sub Saharan Africa was 18.9% this finding was higher than a review conducted in Africa [ 61 ]. The prevalence of postpartum depression varies in sub regions of Sub Saharan Africa, which was 20.2% in western Africa, 18.6% in Eastern Africa and 18.3% in southern Africa.…”
Section: Discussioncontrasting
confidence: 81%
“…5,19 Our study showed that there is increased incidence of postpartum depression in upper lower class (46%) when compared to upper middle class (32%), and this study was supported by study conducted by Abel Fekadu et al, showed that low socioeconomic status was the significant contributing factor for development of postpartum depression. 16 Our study did not show any association between the literacy rate and risk of developing PPD, However, the other study conducted by Shafi et al, showed that there is decreased rate of PPD among graduates and among post graduates and it could be because of their self-esteem and better interpersonal relationship. Women from urban area are having more independent life and better life style choices, could act as a protective factor from mood disturbances during pregnancy.…”
Section: Discussioncontrasting
confidence: 78%